Limosilactobacillus reuteri in immunomodulation: molecular mechanisms and potential applications - Luo, Zichen; Chen, Ailing; Xie, Anni; Liu, Xueying; Jiang, Shanyu; Yu, Renqiang (Frontiers in Immunology, 2023)
Frequent use of hormones and drugs may be associated with side-effects. Recent studies have shown that probiotics have effects on the prevention and treatment of immune-related diseases. Limosilactobacillus reuteri (L. reuteri) had regulatory effects on intestinal microbiota, host epithelial cells, immune cells, cytokines, antibodies (Ab), toll-like receptors (TLRs), tryptophan (Try) metabolism, antioxidant enzymes, and expression of related genes, and exhibits antibacterial and anti-inflammatory effects, leading to alleviation of disease symptoms. Although the specific composition of the cell-free supernatant (CFS) of L. reuteri has not been clarified, its efficacy in animal models has drawn increased attention to its potential use. This review summarizes the effects of L. reuteri on intestinal flora and immune regulation, and discusses the feasibility of its application in atopic dermatitis (AD), asthma, necrotizing enterocolitis (NEC), systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and multiple sclerosis (MS), and provides insights for the prevention and treatment of immune-related diseases.